The kinematics chain of instep kicking of soccer with upperbody constrained: a pilot study - Chen, Y.; Chang, J. H.; Lin, H. T. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to understand the kicking performance when the upperbody motion has been limited. One player in the college cup level A volunteered to participate in this study (Aged: 20 years, Height: 172 cm, Body mass: 65 kg). A VICON motion capture system (200 Hz) was used to capture the kicking motion. The participant was asked to kick the ball both using an arm swing and not using an arm swing. The Visual3D was used to calculate the segment velocity, angular velocity, and kinetic chain. The results indicated that kicking with arm swing had a greater ball and lower-extrimity segment velocity. The main effect for lower ball velocity during kicking without arm swing is the decreased angular velocity at the ankle joint. When arm motion has been limited, players should noticed that the ankle joint needs to follow through after foot-ball contact.